2019
DOI: 10.1109/jphot.2019.2950472
|View full text |Cite
|
Sign up to set email alerts
|

Lumen Degradation Lifetime Prediction for High-Power White LEDs Based on the Gamma Process Model

Abstract: Nowadays, due to the advancement of design and manufacturing technology, there are many consumer products with high reliability. Similarly, the competition in the business sector influences the product development time to become shorter and that makes it difficult for manufacturers to evaluate the reliability of current products before new products are released to the market. This phenomenon is manifested in the lighting industry, especially for the high power white light-emitting diodes (LEDs) as these produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Apart from algorithmic innovations for general applications, a large proportion of research outcomes also focuses on the RUL prediction of specific components or devices, for instance, power transformers and transducers [71], [75], [79]; supercapacitors [78], [80]; transistors (MOSFET, IGBT) and diodes [62], [70], [81]; bearings [66], [67], etc. Other previous review can be found in [82], [83], [60], [84], [77] and the references therein.…”
Section: B Rul Estimation Approachesmentioning
confidence: 99%
“…Apart from algorithmic innovations for general applications, a large proportion of research outcomes also focuses on the RUL prediction of specific components or devices, for instance, power transformers and transducers [71], [75], [79]; supercapacitors [78], [80]; transistors (MOSFET, IGBT) and diodes [62], [70], [81]; bearings [66], [67], etc. Other previous review can be found in [82], [83], [60], [84], [77] and the references therein.…”
Section: B Rul Estimation Approachesmentioning
confidence: 99%
“…Nevertheless, it is worth noting that the gamma process appears suitable for the monotonic degradation process, and this may Reproduced with permission. [125] Copyright 2019, IEEE.…”
Section: Gamma Process-based Approachmentioning
confidence: 99%
“…Recently, the gamma process has been employed to model the lifetime of high-power white LEDs based on CCT shift. [124] Ibrahim et al [125] also used gamma process to model reliability of phosphor-converted white LEDs by estimating the long-term lumen maintenance lifetime and validate by comparing with the NLS regression method. The results showed that the prediction accuracy of the gamma process was superior compared with the NLS regression-based approach.…”
Section: Gamma Process-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-State lighting is one of the most promising lighting technologies in the 21st century, and has become the dominant technology for the general lighting [1]. The solid-state lighting technology based on light-emitting diodes (LEDs) and laser diodes (LDs) has gained widespread attention [2], [3]. In recent years, LEDs are replacing conventional incandescent lamps due to several well-known advantages, such as color-tunable property, long lifespan, compact size, and high luminous efficacy among others [4], [5].…”
Section: Introductionmentioning
confidence: 99%